THE FEAST OF ENLIGHTENMENT AND FAMINE OF THE SELF (ENCOUNTER WITH THE OTHER IN THE AUTOBIOGRAPHY OF DOSITEJ OBRADOVIĆ) - Aleksandra S. Sekulić (Filolog, 2025)
This paper interprets the idea of feast and hospitality in The Life and Adventures of Dimitrije Obradovic: Who as a Monk Was Given the Name Dositej. Analysing the figures of friendship, one comes to the constitutive elements of Dositej’s autonarrative that reveal a special kind of hunger and emptiness in the place where the representative self-sufficiency of the enlightened mind is expected. Enlightenment ideology of friendship also conditions the encounter with the Other, which is why in Dositej's text the friend always appears as the one who welcomes and hosts, but also the one who discovers that the subject itself does not exist outside of representativeness, outside of exemplarity. Feeding himself in the meeting with his friends, Dositej feeds his own text, remaining, in fact, the subject of hunger, essentially unsatiated and hidden behind the discourse of the Enlightenment.